Primary mediastinal non- Hodgkin’s lymphoma (NHL) directly invading into the superior vena cava and the right atrial chamber. - Chiranjib Nag; Mrinalkanti Ghosh; Soumitra Ghosh (Mediterranean Journal of Hematology and Infectious Diseases)
Lymphomas are common mediastinal neoplasms. NHL that involves the mediastinum usually manifests with diffuse lymphedenopathy involving the anterior, middle and occasionally posterior mediastinal nodal groups, large tumours causing SVC obstruction, compression of airway and chest wall invasion are documented in literature. However there are rare instances where NHL is directly invading into the heart chamber.